PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KERJA KARYAWAN TOSERBA BERKAH JAYA CIPARI - Ernawati (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This research is a survey research on the work motivation of the employees of the Berkah Jaya Cipari Department Store in Cilacap. This study takes the title: